Belize : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Belize. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Belize focused on structural reforms to raise growth and social inclusion; strengthening resilience to natural disasters; balanced medium-term fiscal consolidation; tax reform; and strengthening financial oversight and anti-money laundering and combating the financing of terrorism actions. Public debt remains above 90 percent of gross domestic product, the current account deficit is projected to remain large over the medium term, and international reserves are just below three months of imports of goods and services. The pace of structural reform has been slow. Downside risks, including from slower US growth, natural disasters, crime, and renewed pressures on correspondent banking relationships could weaken growth and financial stability. Belize is adapting its tax regime in response to concerns from multilateral institutions regarding potentially harmful features. Sustaining Belize's recent economic expansion, spurring private investment, and facilitating structural diversification hinges on strengthening the business environment.